HUBUNGAN ANTARA TINGKAT PENDIDIKAN IBU, KEPERCAYAAN TERHADAP TABU MAKANAN, DAN STATUS GIZI IBU DENGAN PEMBERIAN ASI EKSKLUSIF DI KELURAHAN LIMO DAN SAWANGAN KOTA DEPOK - Tyara Rally Athiyyah Nabila, (2023)
Exclusive breastfeeding (EBF) is recommended by World Health Organization (WHO) for babies in the first 6 months of life. Exclusive breastfeeding can be influenced by several factors, including the education level of the mother, belief in food taboos, and also the nutritional status of the mother. This study aims to analyze the relationship between the education level of the mother, belief in food taboos, and also the nutritional status lactating mother with exclusive breastfeeding in Limo and Sawangan, Depok City. This is an analytic observational study with a cross-sectional design. The population in this study are lactating mothers in Limo and Sawangan area of Depok City. The sample taken by cluster sampling technique to 216 respondents. The data collected using a questionnaire and analyzed using the chi-square test. The results of this study indicated that there is no relationship between the education level of the mother (p-value = 0,881), belief in food taboos (p-value = 0,671), and also the nutritional status of the mother (p-value = 0,345) to exclusive breastfeeding. Health stakeholders should provide education regarding the importance of fulfilling exclusive breastfeeding